Propagation of Cardamom (Amomum compactum) Using Vitamin B1, Indole Butyric Acid and Their Combinations Ex Vitro - Azka Mutiara Salsabila; Lukita Devy; Dasumiati Dasumiati (UIN Sunan Gunung Djati Bandung, 2024)
Cardamom (Amomum compactum) is an aromatic spice plant with numerous benefits, widely used in cooking, medicine, and beverages. The high demand for cardamom remains unmet due to the lengthy germination period required for cardamom seeds and the inability of cardamom shoots to thrive when planted independently from the mother plant. The presence of the mother plant significantly impacts cardamom nurseries utilizing shoots, making it challenging to obtain large quantities of nursery transplants. Growth stimulants, such as vitamin B1 and Indole Butyric Acid (IBA), are required to enÂhance vegetative growth in plants. Vitamin B1 (IPI brand) is applied due to its ease of accessibility and cost-effectiveness. Meanwhile, IBA is utilized for its accessibility, stable chemical content, and prolonged efficacy. This research aims to determine the optimal concentration of vitamin B1, IBA, and their combination to enhance the growth of mother and tiller shoots of cardamom ex vitro. The research employed a two-factorial Randomized Complete Block Design, with vitamin B1 concentrations of 21.5% and 43% and IBA concentrations of 0.75 ppm and 150 ppm. The treatment V1I1 (vitamin B1 21.5% and IBA 75 ppm) on mother plant shoots maintained a survival rate of 67% up to 12 Weeks After Planting (WAP). The interaction between vitamins B1 and IBA exhibited no significant effect on all parameters of mother shoots and tillers; however, vitamin B1 significantly influenced the vegetative growth of cardamom mother shoots. Vitamin B1 at 43% produced a significantly higher number of leaves compared to 21.5%. Thus, vitamin B1 at 43% is recommended for cardamom propagation, while vitamin B1 at 21.5% has the potential to enhance the average growth of tiller shoots across all parameters.